Efektivitas Perangkat Pembelajaran Fisika Berbasis Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah dan Kemampuan Berpikir Kritis Peserta Didik - Winda Astarini Aripin; Hairunisyah Sahidu; Muhammad Makhrus (Prodi Fisika FKIP Unram, 2021)
This study aims to determine the effectiveness of physics learning tools based on problem based learning models to improve effective and efficient problem solving and critical thinking skills of students. The type of research used is research and development (Research and Development) with the research model being developed is 4D Models. The effectiveness is obtained from a limited trial to get the N-gain test value and the efficiency is determined from the student's response. The results of the study based on the results of the average N-gain test obtained a value of 0.41 with a medium category. Student responses showed that they were not satisfied with online learning. So it can be concluded that the effectiveness of the physics learning device model of problem based learning on harmonic vibration material is effective and efficient for improving problem solving abilities and critical thinking skills of students.